Fungsi Perencanaan dalam Manajemen terhadap Optimalisasi Layanan Bimbingan dan Konseling - Berlima Pasaribu; Uman Suherman (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Guidance and Counseling Management cannot be separated from planning. A good planning process will have an impact on the optimization of guidance and counseling services, whereas unsystematic planning will greatly affect the quality of guidance and counseling services. One of the impacts is that guidance and counseling services only focus on handling problematic students and this is not in line with the purpose and function of guidance and counseling in schools. This study aims to look at the description of guidance and counseling planning and its relation to the optimization of guidance and counseling services for counselees on Nias Island. The method used in this research is descriptive qualitative with the type of case study research in four schools on Nias Island. The research was conducted with interviews and documentation conducted online. The research subjects were guidance and counseling teachers from vocational and junior high schools. The results show that planning in educational institutions located on Nias Island shows a lack of systematic and efficient planning. This deficiency in planning has significant implications for the improvement of guidance and counseling services in schools. The focus of Guidance and Counseling Services is only on students who have problems, this shows that services are not optimal and have an impact on counselees who need services for self-development and also preventive functions. Therefore, this research is expected to be an input to improve guidance and counseling planning in schools. Furthermore, it is important for every principal and teacher to have involvement to maximize services to students.